The legacy of Nazi occupation : patriotic memory and national recovery in Western Europe, 1945-1965 - Lagrou, Pieter (Studies in the social and cultural history of modern warfare., 1999)
This book analyses how France, Belgium and the Netherlands emerged from the Second World War. Pieter Lagrou offers a genuinely comparative approach, based on extensive archival research. Brilliantly researched and fluently written, this book will be of central interest to all scholars and students of twentieth-century European history.